2020
DOI: 10.1101/2020.05.31.115741
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

INGOT-DR: an interpretable classifier for predicting drug resistance in M. tuberculosis

Abstract: 15Motivation: The prediction of drug resistance and the identification of its mechanisms in bacteria 16 such as Mycobacterium tuberculosis, the etiological agent of tuberculosis, is a challenging problem. 17 Modern methods based on testing against a catalogue of previously identified mutations often yield 18 poor predictive performance. On the other hand, machine learning techniques have demonstrated 19 high predictive accuracy, but lack interpretability to aid in identifying specific mutations which lea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…To evaluate the efficacy of the gene-centric approach, we applied the same methods to the SNP-based dataset (Section 2.6). Using SNP data, we trained and tested the state-of-the-art methods [13, 14, 15, 19]. We found that the LRCN approach on the SNP data performed similarly to other methods (Figure 5b).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…To evaluate the efficacy of the gene-centric approach, we applied the same methods to the SNP-based dataset (Section 2.6). Using SNP data, we trained and tested the state-of-the-art methods [13, 14, 15, 19]. We found that the LRCN approach on the SNP data performed similarly to other methods (Figure 5b).…”
Section: Resultsmentioning
confidence: 89%
“…In order to compare our method to state-of-the-art methods, we use an LSTM, a wide-n-deep neural network (WnD) [19], a support vector machine (SVM), logistic regression (LR), and random forests (RF) [19, 13, 14, 15]. We did not compare to k-mer based approaches such as KOVER [39] as they are out of the scope of the SNP-based paradigm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate about how to define and calculate ECOFF/ECVs will continue and new approaches will be suggested (44)(45)(46)(47). However it evolves, larger and more geographically diverse tuberculosis datasets, such as presented here, will bring more confidence and rigour to the antibiotic susceptibility testing of clinical tuberculosis samples.…”
Section: Discussionmentioning
confidence: 98%
“…In future work, we plan to extend SplitStrains to work with other bacterial pathogens as well as to improve its resolution, at least in datasets with a high depth of coverage. Lastly, we plan to use SplitStrains as a preprocessing step in two pipelinesone for identifying related isolates in an outbreak [23], where mixed infections can mask such relatedness, and another one for predicting drug resistance [24], where mixed infections can impede a correct prediction when only the minor strain is drug-resistant.…”
Section: February 1 2021mentioning
confidence: 99%